Study on the Selection Model of Staying Adjustment Bus Lines along Rail Transit - Jie Cui; Yueer Gao; Jing Cheng; Lei Shi (Journal of Advanced Transportation)
To fully achieve effective rail transit, prevent the waste of conventional bus capacity along a rail transit line, and relieve the urban traffic congestion problem, it is necessary to screen for the adjustment of conventional bus lines prior to the operation of rail transit to provide a basis for further optimization of bus lines. Based on the analysis of spatial relationships between a rail transit line and conventional collinear bus lines and considering the time advantage characteristics of rail transit in rush hours, a model of the generalized travel time costs and travel time savings proportion in the collinear section of rail transit and bus was proposed. To evaluate the utility of rail transit relative to conventional bus collinear lines, the conventional bus lines to be adjusted were determined. Taking Xiamen as an example, the bus lines of Hubin East Road Station as the endpoint of metro line 1 were employed to calculate the model using GPS data of the buses, and the bus lines to be adjusted in the Hubin East Road were determined. The results show that the model is effective in the elastic selection of conventional bus lines that need to be adjusted and provides decision-making support for urban comprehensive public transport planning.